Abdominal angiostrongyliasis: a case with severe evolution Angiostrongilíase abdominal: um caso com grave evolução - José Wellington Alves dos Santos; Ricardo Morgental Zambenedetti; Keli Cristina Mann; Marta Pires da Rocha; Ewerton Nunes Morais; Carlos Graeff-Teixeira (Revista do Instituto de Medicina Tropical de São Paulo, 2005)
A case of acute abdomen disease caused by abdominal angiostrongyliasis is reported. A 42-year-old otherwise healthy patient presented with a complaint of nine days of abdominal pain, constipation, disury, fever and right iliac fossa palpable mass. Exploratory laparotomy was performed. After surgical treatment the patient presented serious complications. É relatado um caso de abdome agudo causado por angiostrongilíase abdominal. Um paciente de 42 anos, previamente hígido, apresentou queixa de nove dias de dor abdominal, constipação, disúria, febre e uma massa palpável na fossa ilíaca direita. Uma laparotomia exploradora foi realizada. Após o tratamento cirúrgico o paciente apresentou graves complicações.